KMS Protoype using Stohmaier Framework at Association of Indonesian Kindergarten Teachers in South Bangka Regency - Raya, Agustina Mardeka; Sulaiman, Rahmat (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
IGTKI is a kindergarten teacher association organization that aims to realize the quality of early childhood education with a spirit of professional love and character to be able to face the era of globalization. However, this goal is not fully implemented because of the distance of each school is far, the results of the training are not socialized, the lack of knowledge to handle students with special needs so that the lack of knowledge sharing among PAUD teachers. To increase the knowledge sharing needed a Knowledge Management System application that can be a solution of knowledge sharing that is not hindered by the limitations of time and place. This study uses the Strohmaier Framework for modeling knowledge management systems. Techniques of Analysis and system design are carried out using the object oriented approach method Unifed Manipulation Language (UML). The suitability of the system to the business process was tested using the Forum Group Discussion (FGD) method which was validated using the Fit criteria from Strohmaier's theory which produced a value of 76%, this value shows that the Knowledge Infrastructure designed is in accordance with the business process. Meanwhile, user acceptance of the system was tested using User Acceptance Testing (UAT) in the form of a questionnaire which was calculated based on the Linkert scale, producing a value of 84%. From this value it can be concluded that the level of user acceptance at IGTKI is good for the KMS created.